Renal traumas in childhood: a five years experience of tertiary care hospital in Turkey - Tuncer, Ahmet A.; Gökbaş, Hülya; Deniz, Samet; Ozkan, Elif; Kocataş, Hüsne B.; Kahya, Onur C.; Demirci, Şeyma N.; Boyacı, Evrim Ozkaraca; Embleton, Didem Baskın; Çetinkurşun, Salih (International Surgery Journal, 2018)
Background: In this study, the experiences of kidney trauma of a third step hospital in a city at the junction of the road will be discussed with the current literature. Methods: Pediatric trauma patients admitted to Afyon Kocatepe University Hospital between 1 January 2012 and 31 December 2017 were retrospectively examined. Thirty patients with renal injuries were included in the study. Patients with renal injury were examined in terms of age, gender, type of trauma, degree of renal injury, additional organ damage, treatment method, duration of hospitalization, cost and mortality. Statistical analysis was performed with the SPSS program. The p >0.05 was considered as significant. Results: A total of 30 patients (m:23, f:7) were included in the study. The mean age of the patients was 12.10±5.70. The mean duration of hospitalization was 10.23±17.067 days. The reasons of kidney injury were determined as; traffic accident outside of the vehicle (n=9), fall (n=8), traffic accident inside the vehicle (n=6), bicycle-motorcycle accident (n=5), and firearm injury (n=2). Hematuria (n=8), grade 1 (n=12), grade 2 (n=2), grade 4 (n=5), and grade 5 (n=3) kidney injuries were detected in the patients. Isolated renal injuries were found in 7 patients. Additional organ injuries were found as lung injury (n=3), head injury (N=5), pelvic injury (n=5), spleen injury (n=8), spine injury (n=7), liver injury (n=7), intestinal injury (n=7), and extremity injury (n=7). The average cost was 4948.37 ± 10198.51 TL. One patient had nephrectomy and JJ catheter was placed to one patient due to the development of urinoma and hematoma. All other patients were treated conservatively. The cost and duration of hospitalization of patients with shock status at the time of admission to the hospital were statistically higher than those without shock status (p=0.001; p=0.025). Morbidity and cost of patients with high grades (grade 4 or 5) were higher than those with low grades (p=0.008 and p=0.027, respectively). There was no mortality except for a patient who underwent splenectomy and had concomitant brain parenchymal damage. Conclusions: Conservative treatment of kidney injuries for children is effective and safe. Additional injuries, shock status and high-grade cause morbidity, mortality and cost increases.